AB0332 Golimumab Efficacy in Rheumatoid Arthritis after Conventional and Biological Treatment: Data from The Italian Lorhen Registry. (15th July 2016) - Grosso, V.; Gorla, R.; Sarzi-Puttini, P.; Atzeni, F.; Pellerito, R.; Fusaro, E.; Paolazzi, G.; Rocchetta, P.A.; Favalli, E.G.; Marchesoni, A.; Caporali, R.
Abstract : Background: The efficacy of Golimumab (GLM) treatment in rheumatoid arthritis (RA) has been widely documented in clinical trials. Data are still needed to assess its efficacy and tolerability in everyday clinical practice. Objectives: To assess the efficacy of the treatment with GLM in RA previously treated with conventional synthetic disease modifying antirheumatic drugs (csDMARDs) or biological DMARDs (bDMARDs) from a multicentric observational cohort (the LORHEN Registry). Methods: All patients with a diagnosis of RA in the LORHEN database who started GLM from october 2010 up to september 2015, with at least one reported visit, were included. We reviewed the data regarding the first 24 months of treatment, focusing on clinical efficacy. The efficacy of GLM was assessed with DAS28, DAS28(CRP), SDAI and EULAR response criteria. We executed intention-to-treat (ITT) and per-protocol analysis (PP). We repeated the analysis for the subgroups of patients who received GLM as first or second bDMARD. Results: We retrieved the data regarding 180 patients, with a mean (sd) age of 54, 57 (13, 62) years and a mean (sd) disease duration of 9, 52 (9, 32) years. Methotrexate was the concomitant csDMARD for 123 (68, 3%) patients, while leflunomide, sulfasalazine and cyclosporine were given to 13 (7, 2%), 5 (2, 8%) and 4 (2, 2%) patients respectively. 35 (19, 4%) patients were treated with GLM monotherapy. 137 (76, 1%) and 5 (2, 8%) patients were given low dose (≤10mg prednisone equivalent a day) and medium dose (≥10 and ≤25) corticosteroid at baseline, with following tapering. A total of 79 patients stopped the treatment with GLM due to inefficacy or adverse events before 24 months of treatment. With the ITT design 55 (30, 6%) and 44 (24, 4%) patients achieved good or moderate EULAR response respectively at 6 months. The mean (sd) DAS28, DAS28(CRP) and SDAI progressively reduced, reaching 2, 61 (1, 11), 2, 41 (0, 72) and 4, 62 (3, 80) respectively at 24 months. Within the PP scenario, 32 (66, 7%) and 9 (18, 8%) patients reached and maintained good or moderate EULAR response respectively to the end of the follow-up. The clinical response to GLM therapy resulted slightly reduced when given as a second line bDMARD treatment, but the data did not met statistical significance. Conclusions: GLM is effective in treating RA in everyday clinical practice. The efficacy increases significantly over the first 6 months and slightly during the following 18 months. Interestingly enough, patients treated with GLM after a first bDMARD can still achieve low disease activity and clinical remission, with an overall efficacy of the treatment not statistically different to the first line. Disclosure of Interest: None declared